2015
DOI: 10.4097/kjae.2015.68.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Use of triazolam and alprazolam as premedication for general anesthesia

Abstract: BackgroundTriazolam has similar pharmacological properties as other benzodiazepines and is generally used as a sedative to treat insomnia. Alprazolam represents a possible alternative to midazolam for the premedication of surgical patients. The purpose of this study was to evaluate the anxiolytic, sedative, and amnestic properties of triazolam and alprazolam as pre-anesthetic medications.MethodsSixty adult patients were randomly allocated to receive oral triazolam 0.25 mg or alprazolam 0.5 mg one hour prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
2
17
0
1
Order By: Relevance
“…Flumazenil has a major advantage of benzodiazepines compared to other sedative drugs, with a rapid antagonistic effect on sedatives, easily reversing sedation. 1,2,10,20,25 Cardiovascular reactions are common in surgical situations and may be related to the response to the activation of α and β-adrenergic receptors, resulting in increased cardiac output, increased peripheral vascular resistance and a possible increase in blood pressure and heart rate, varying from individual to individual. This difference reflects the variability in the adrenal sympathetic activation, which leads to the release of epinephrine and norepinephrine during a stressful situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flumazenil has a major advantage of benzodiazepines compared to other sedative drugs, with a rapid antagonistic effect on sedatives, easily reversing sedation. 1,2,10,20,25 Cardiovascular reactions are common in surgical situations and may be related to the response to the activation of α and β-adrenergic receptors, resulting in increased cardiac output, increased peripheral vascular resistance and a possible increase in blood pressure and heart rate, varying from individual to individual. This difference reflects the variability in the adrenal sympathetic activation, which leads to the release of epinephrine and norepinephrine during a stressful situation.…”
Section: Discussionmentioning
confidence: 99%
“…Its main effects are the reduction of anxiety and panic attacks in patients, thus being a possible alternative premedication for surgical patients. 25 Alprazolam is an anxiolytic agent used as pre-medication due to its short half-life, rapid effect and ease of use when compared to other benzodiazepines. 26 Its effect lasts for about 1-2 hours and it has a lower incidence of paradoxical effects or anterograde amnesia, being a good alternative to sedation.…”
Section: Literature Review Benzodiazepinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Они проявляют противогрибковый (флуко-назол, интраконазол, вориконазол) [1], противо-воспалительный [2], седативный (триазолам, алфа-золам) [3], и противомикробный эффекты [4]. Среди меркапто-и тион-замещенных 1,2,4-триазо-лов было зарегистрировано большое число произ-водных, проявляющих антибактериальные [5,6], фунгицидные [7,8], противотуберкулензые [9] и антимикобактериальные [10] свойства, противора-ковую активность [11,12].…”
unclassified
“…The study concluded that there were no significant differences between two groups with respect to anxiety and sedation but amnesic property was seen in triazolam treated patients but not by alprazolam treated patients. 15 White PF et al conducted a study in which midazolam (0.5 mg /kg IV) was found to produce a spectrum of central nervous system activity like sedation and amnesia that was similar to diazepam (0.1-0.3 mg/kg IV). However the slope of midazolam dose response curve for sedation appears to be steeper.…”
mentioning
confidence: 99%